2013
DOI: 10.1002/hbm.22386
|View full text |Cite
|
Sign up to set email alerts
|

Pattern classification of response inhibition in ADHD: Toward the development of neurobiological markers for ADHD

Abstract: The diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) is based on subjective measures despite evidence for multisystemic structural and functional deficits. ADHD patients have consistent neurofunctional deficits in motor response inhibition. The aim of this study was to apply pattern classification to task-based functional magnetic resonance imaging (fMRI) of inhibition, to accurately predict the diagnostic status of ADHD. Thirty adolescent ADHD and thirty age-matched healthy boys underwent fMRI whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 69 publications
9
92
2
5
Order By: Relevance
“…This is the first volumetric study in ADHD adult population that has shown smaller GM in the SMA. Functional neuroimaging studies suggest that a network of fronto-parietal brain regions -including the inferior prefrontal, medial prefrontal (the SMA and pre-SMA) and inferior parietal areas, are implicated in motor response inhibition (Hart et al, 2013), with SMA as one of the key motor inhibition areas (Hart et al, 2014). This may be significant, since some psychological theories have proposed that ADHD symptoms result from a primary deficit in inhibitory control (Barkley, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…This is the first volumetric study in ADHD adult population that has shown smaller GM in the SMA. Functional neuroimaging studies suggest that a network of fronto-parietal brain regions -including the inferior prefrontal, medial prefrontal (the SMA and pre-SMA) and inferior parietal areas, are implicated in motor response inhibition (Hart et al, 2013), with SMA as one of the key motor inhibition areas (Hart et al, 2014). This may be significant, since some psychological theories have proposed that ADHD symptoms result from a primary deficit in inhibitory control (Barkley, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Increased activity has been observed in regions constituting the default mode network (DMN), whose activation is normally reduced during tasks and increased during resting‐state in typically developing participants . Multivariate pattern recognition analysis of inhibition networks based on task‐based functional MRI was proposed as a potential complementary diagnostic tool for ADHD . Nevertheless, meta‐analyses and individual studies have also reported increased inhibition‐related activity in regions typically showing a reduced activation in ADHD during inhibition tasks, such as the inferior frontal gyrus, suggesting that response‐inhibition related activity in children with ADHD cannot at this time be considered as a systematic biomarker for ADHD.…”
Section: Structural Brain Imaging In Adhdmentioning
confidence: 99%
“…Recently, an increasing number of studies have focused on applying MVPA to discriminate brain disease at the individual level. Some success has been achieved in the study of major depressive disorder (Liu et al, 2012), Alzheimer's Disease (Liu et al, 2014) and attention-deficit hyperactivity disorder (Hart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%